DETERMINATION OF ELECTRONIC DISTANCE MEASUREMENT ZERO ERROR USING KALMAN FILTER - Okwuashi, Onuwa; Olayinka, Dupe Nihinlola (European Scientific Journal, ESJ, 2014)
Kalman filter has gained popularity in the adjustment of field measurements since it was invented in 1960. Unlike the least squares technique it is relatively not renowned in the adjustment of surveying measurements. This work presents how it can be used in the determination of the electronic distance measurement zero error. First the values of the unknown parameters and their corresponding covariances are predicted. Subsequently, updates on the predicted parameters and covariances are estimated in several iterations. The residuals are estimated to determine the accuracy of the experiment. The estimated electronic distance measurement zero errors for three epochs are 0.015033522833m, 0.0113142487320m and 0.0113121989063m.